The use of dietary supplements, stimulants, medications and associated factors among paddle tennis players - Da Silva Mendes Huber, A. C.; Schuelter Trevisol, F.; Huber, M. P.; De Souza, F.; Trevisol, D. J. (Asian Journal of Sports Medicine, 2019)
Background:Medications for pain and inflammation have increased lately, and dietary supplements and stimulants have increasingly been used to maximize sports performance. They can be harmful to health if they are unnecessary or misused.